2021
DOI: 10.1111/ijcp.14002
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive dexmedetomidine infusion in open living donor hepatectomy: A way to enhance postoperative analgesia and recovery

Abstract: Open living donor hepatectomy (OLDH) is an intensely painful procedure, with moderate-to-severe pain during the first 2 days after surgery; furthermore, 31% and 27% of donors have developed persistent pain by 6 and 12 months after OLDH, respectively. 1 Inadequate control of perioperative pain will affect the overall quality of life and may contribute to chronic pain. Therefore, advanced strategies should be used to enhance perioperative analgesia and postoperative recovery in patients undergoing OLDH.Enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Craniocerebral surgery is required for brain tumors, severe brain trauma, cranial deformation, encephalorrhagia, and other diseases, which is a common brain surgery, but with a high risk due to the special surgical sites [ 13 15 ]. Before surgery, patients should be routinely examined to select the appropriate anesthesia and surgical methods, mainly including the detection of the cerebral metabolism, intracranial pressure, and cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Craniocerebral surgery is required for brain tumors, severe brain trauma, cranial deformation, encephalorrhagia, and other diseases, which is a common brain surgery, but with a high risk due to the special surgical sites [ 13 15 ]. Before surgery, patients should be routinely examined to select the appropriate anesthesia and surgical methods, mainly including the detection of the cerebral metabolism, intracranial pressure, and cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…There were no reported technical difficulties or complications of regional or neuroaxial techniques in these cohorts. Adjuvant pharmacological therapies investigated were: Dexmedetomidine, a potent alpha‐2 agonist with hypnotic, sedative, and analgesic properties; ketamine, a NMDA receptor antagonist with sedating, analgesic, and hypnotic actions; intravenous lidocaine, a sodium channel blocker with analgesic properties; ketorolac, a non‐steroidal anti‐inflammatory drug; and parecoxib, a cyclo‐oxygenase‐2 inhibitor 9,11–15 . A single feasibility study investigated the role of acupuncture in this setting and concluded that the delivery of acupuncture was possible in this cohort of patients 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Post‐operative pain scores were reported in eight studies (Table 2 and Supplementary Table S1). Four out of five studies included a control group and showed a significantly lower pain score at 24 h 9,11–13 . The multi‐modal approach by Hardman et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that systemic DEX could prolong the duration of analgesia. 23,24 Additional sciatic nerve block could prolong the duration of analgesia for relieving postoperative pain. In our study, the duration of analgesia between the two groups was similar.…”
Section: Discussionmentioning
confidence: 99%